Penyuluhan Upaya Pencegahan Dan Deteksi Dini Terhadap Permasalahan Hipertensi Pada Komunitas Lansia Di Kelurahan Kauman Surakarta - Panggih Priyo Wicaksono; Wahyuni Wahyuni; Amalia Faradilla Rahim (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Hypertension is a disease that always receives attention in the world, because hypertension is one of the biggest causes of morbidity in the world. Based on data from the Health Office, (2018) Central Java is ranked in the top 10 for hypertension, and data on the percentage of hypertension in Surakarta City in 2018 was 67,827 cases. The method used is to provide education on prevention and early detection of hypertension problems in the elderly community in Kauman sub-district, Surakarta. The aim of this program is to increase public knowledge and understanding regarding hypertension. The results of hypertension counseling in the elderly community of Kauman Subdistrict, Surakarta, participants' enthusiasm, motivation and curiosity were very high, and after being given the counseling the participants understood better and felt helped in handling and knowing about hypertension.